Western diet-induced hepatic steatosis and alterations in the liver transcriptome in adult Brown-Norway rats. Issue 1 (December 2015) - Roberts, Michael; Mobley, C.; Toedebush, Ryan; Heese, Alexander; Zhu, Conan; Krieger, Anna; Cruthirds, Clayton; Lockwood, Christopher; Hofheins, John; Wiedmeyer, Charles; Leidy, Heather; Booth, Frank; et al.
Abstract Background The purpose of this study was to investigate the effects of sub-chronic high fat, high sucrose diet (also termed 'Westernized diet' or WD) feeding on the liver transcriptome during early nonalcoholic fatty liver disease (NAFLD) development. Methods Brown Norway male rats (9 months of age) were randomly assigned to receive ad libitum access to a control (CTL; 14 % kcal fat, 1.2 % sucrose by weight) diet or WD (42 % kcal from fat, 34 % sucrose by weight) for 6 weeks. Results Six weeks of WD feeding caused hepatic steatosis development as evidenced by the 2.25-fold increase in liver triacylglycerol content, but did not induce advanced liver disease (i.e., no overt inflammation or fibrosis) in adult Brown Norway rats. RNA deep sequencing (RNA-seq) revealed that 94 transcripts were altered in liver by WD feeding (46 up-, 48 down-regulated, FDR < 0.05). Specifically, the top differentially regulated gene network by WD feeding was 'Lipid metabolism, small molecular biochemistry, vitamin and mineral metabolism' (Ingenuity Pathway Analysis (IPA) score 61). The top-regulated canonical signaling pathway in WD-fed rats was the 'Superpathway of cholesterol biosynthesis' (10/29 genes regulated, p  = 1.68E-17), which coincides with a tendency for serum cholesterol levels to increase in WD-fed rats (p  = 0.09). Remarkably, liver stearoyl-CoA desaturase (Scd ) mRNA expression was by far the most highly-induced transcript in WD-fed rats (approximately 30-fold, FDR = 0.01) which supports previous literature underscoring this gene as a crucial target during NAFLD development. Conclusions In summary, sub-chronic WD feeding appears to increase hepatic steatosis development over a 6-week period but only induces select inflammation-related liver transcripts, mostly acute phase response genes. These findings continue to outline the early stages of NAFLD development prior to overt liver inflammation and advanced liver disease.